Development of a Simplified One-Dimensional Model of Humidity in the Cabin of a Passenger Aircraft Based on an Experiment - Tomasz Janusz Teleszewski; Katarzyna Gładyszewska-Fiedoruk (Atmosphere)
This publication presents the results of research on air humidity in the cabin of a passenger aircraft and develops a simplified model of absolute humidity during an aircraft flight as a function of time, number of passengers, aircraft cabin volume, number of air changes, moisture generated by passengers, initial air humidity, and supply air humidity. Based on the measurement results and the developed model, the humidity generated by a single passenger was estimated at 35 g/h, while the number of air changes in the aircraft cabin ranged from 10 L/h to 19 L/h. In order to increase the humidity in the aircraft cabin, it was proposed to modify the ventilation system by adding a humidifier chamber to the supply duct, a controller with the developed model implemented, and a humidity sensor in the aircraft cabin and the supply duct. The value of absolute humidity in the air supplied behind the humidifier chamber can be determined based on the presented algorithm. The developed model based on the humidity balance in the cabin of a passenger aircraft can be used in algorithms for automatic regulation of ventilation in passenger aircraft.